Purchasing power parity and interest parity in the laboratory - Eric O'N. Fisher (Osaka University, Institute of Social and Economic Research (ISER), 2001)
This paper analyzes purchasing power parity and uncovered interest parity in the laboratory. It finds strong evidence that purchasing power parity, covered interest parity, and uncovered interest parity hold. Subjects are endowed with an intrinsically useless (green) currency that can be used to purchase another useless (red) currency. Green goods can be bought only with green currency, and red goods can be bought only with red currency. The foreign exchange markets are organized as call markets. In the treatment analyzing purchasing power parity, the price of the red good varies. In a second treatment, the interest rate on red currency varies. In a third treatment, the interest rate on red currency varies, and the price of the red good is random.
Keywords: 330; Kaufkraftparität; Zinsparität; Theorie